2007
DOI: 10.1002/anie.200603753
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Complexes of Polymers Bearing Adamantyl Groups: Host–Guest Interactions and the Effect of Spacers on Water Solubility

Abstract: Polymer-inclusion complexes (PICs) with cyclodextrins (CDs) show a broad structural variety [1][2][3][4] and are of interest for many different applications, for example, drug delivery systems [5] and stimuli-responsive hydrogels. [6, 7] We have demonstrated that the lower critical solution temperature (LCST) of N-isopropylacrylamide(NIPAAM)-based copolymers bearing adamantyl groups can be influenced through complexation of the adamantyl moieties by cyclodextrins (CDs). [8,9] Recently, we reported on the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 24 publications
1
61
1
Order By: Relevance
“…Ritter et al already showed that the length of the spacer is crucial for the water solubility of temperature responsive materials based on cyclodextrin complexes. 66 Furthermore, we believe that the maximum catalytic rate will be influenced in a similar way as water solubility. This is why we focussed our efforts on modifying the length of the corresponding crosslinker used.…”
Section: Design Of Ppam-ada-tementioning
confidence: 99%
“…Ritter et al already showed that the length of the spacer is crucial for the water solubility of temperature responsive materials based on cyclodextrin complexes. 66 Furthermore, we believe that the maximum catalytic rate will be influenced in a similar way as water solubility. This is why we focussed our efforts on modifying the length of the corresponding crosslinker used.…”
Section: Design Of Ppam-ada-tementioning
confidence: 99%
“…Since this system indicated low chemical stability, 1-adamantylacrylamide and 6-acryloylaminohexanoic acid-1-adamantylamide were chosen as suitable guest monomers. Additionally, the synthesis of side chain polypseudorotaxanes 39 and 40 were also reported [96]. The incorporation of a flexible hydrophobic spacer between the polymer main chain and the adamantyl moiety strongly affected the thermosensitivity of the supramolecular complex.…”
Section: Side Chain Polypseudorotaxane (Polymer (Polyaxis)/cyclodextrmentioning
confidence: 99%
“…[ 9 , 10 ] Hydrophilic polymers with so-called lower critical solution temperature (LCST) are often described in literature. [11][12][13][14][15][16][17][18][19] But there are only a few reports concerning polymers, which have an upper critical www.mcp-journal.de Macromolecular Chemistry and Physics www.MaterialsViews.com potassium adamantyl carboxylate were dissolved in 2985 μ L of water. During continuous stirring, the transparency of the sample was determined by a voltage controlled semiconductor laser and a silicon photodiode at a wavelength of 500 nm and a heating or cooling rate of 1 ° C min − 1 .…”
Section: Introductionmentioning
confidence: 99%